Follicular Thyroid Cancer With Nose-Tip Metastasis and 131I Uptake. (October 2020) - Yao, Shan-Fan; Lee, Chiang-Hsuan; Chiu, Chuang-Hsin; Fan, Yu-Ming; Huang, Wen-Sheng
Abstract : Abstract: We present a 56-year-old woman with metastatic follicular thyroid cancer at the nose tip with 131 I uptake that is clinically rare, mimicking physiological uptake in the nose, a common finding seen after routine 131 I therapeutic imaging. The lesion revealed a metastatic follicular thyroid cancer with 131 I uptake and response to 131 I therapy. Surgical removal, however, was not performed due to cosmetic and functional considerations. Active surveillance is warranted owing to its relative aggressiveness in nature.